Moderasi Mekanisme Corporate Governance pada Pengaruh Free Cash Flow, Leverage dan Profitabilitas terhadap Manajemen Laba - Agustinus Winoto; A.S.L. Lindawati; Angelia Tantowi (Magister Akuntansi FB-UK.Maranatha, 2022)
The study aims to analyze the corporate governance mechanism in moderating the corrrelation of free cash flow, leverage and profitability on earnings management. The samples in the research are 272 samples based on manufacturing companies that listed on Indonesia Stock Exchange from 2014-2018 which were selected by purposive sampling method. The analytical method is Moderated Regression Analyze. The result of the research, it can be concluded that free cash flow has a negative effect on earnings management, leverage has no effect on earnings management, profitability has a positive effect on earnings management, audit quality was not able to moderate the effect of free cash flow, leverage and profitability on earnings management, managerial ownership able to weaken the effect of free cash flow on earnings management, and managerial ownership not able to moderate the effect of leverage and profitability on earnings management.